The Use of Critical Porosity on Grouping of Rocks Quality of Sandstone Formations - Sigit Rahmawan; Ratnayu Sitaresmi; Suryo Prakoso (Penerbitan Universitas Trisakti, 2019)
Research in the classification of rock quality formations has been carried out by many previous researchers with various methods using core sample data. However, from this research there are still many uncertainties that are found due to the difficulty of the data observed. The study uses the critical porosity for grouping the rock quality. The study obtained evidence on the surface conditions of critical porosity values obtained by the Nur method, et al. Using data P and S wave velocity data on measuring core samples surface pressure conditions that produce different rock quality based on different criticcal porosity ranges. Rock type formed based on the critical porosity has a relation to the pore geometry and pore structure that forms the linkages of each rock type. The similarity of the formation of rock types resulting from the value of critical porosity on rock types using the Wibowo and Permadi methods. In this study ten rock types were obtained. With the formation of rock quality groups that are different from the critical porosity values, further research is needed to find out whether the acoustic log in the data log that has P wave propagation speed can be used to determine the critical porosity value and determine the rock quality classification.